Understanding the impact of chemotherapy on dignity for older people and their partners. (October 2018) - Farrell, Carole; Heaven, Catherine
Abstract: Purpose: Chemotherapy poses challenges for older patients, with potential comorbidities, mobility and functional problems that may adversely affect their dignity. Patients may struggle with side-effects but fail to inform health professionals, impacting on clinical management and unresolved needs/concerns. This study aims to explore the impact of dignity during chemotherapy for older people and partners. Methods: A qualitative study using semi-structured interviews of patients/partners following chemotherapy for non-metastatic cancer. Interviews were audio-recorded, transcribed and analysed using qualitative principles/thematic analysis. Results: Twenty patients, aged 65–81, and 10 partners were recruited. 19/20 patients had adjuvant chemotherapy and one neoadjuvant treatment; 12(60%) had breast cancer and 8(40%) colorectal cancer. Four out of 20(20%) patients failed to complete the full course of chemotherapy and 5(25%) had unplanned hospital admissions. Patients/partners reported positive experiences regarding dignity and compassionate care during chemotherapy. Five main themes were associated with dignity: managing chemotherapy side-effects, personal feelings, maintaining independence, stoicism, and 'being lucky'. Although support from family/friends was high, most patients wanted to maintain their independence and did not want to become a burden. In some cases, patients struggled with chemotherapy toxicities yet often failed to inform clinical staff and played down the severity of adverse effects. This reflected their stoicism, coping strategies and motivations to 'just get on with it'. Conclusions: Dignity is associated with maintaining independence and stoicism in coping with the impact of chemotherapy. However, some patients failed to report severe adverse effects, which has implications for clinical staff managing their care. Highlights: Chemotherapy poses multiple challenges for older people. Some patients had severe toxicities during chemotherapy yet reported positive experiences and compassionate care. Dignity was associated with maintaining independence and stoicism during chemotherapy. Several patients failed to report chemotherapy toxicities to clinicians. Patients were worried about being a burden to their family/friends.